2013
DOI: 10.1590/s1679-62252013000300018
|View full text |Cite
|
Sign up to set email alerts
|

The use of morphological and histological features as nutritional condition indices of Pagrus pagrus larvae

Abstract: Morphometrical and histological techniques were employed to characterize Pagrus pagrus larvae nutritional condition. Larvae were reared in laboratory under controlled conditions with the main objective of testing whether these methodologies allowed finding differences between larvae from different feeding treatments. Once yolk was consumed (three days after hatching) larvae were assigned to a feeding treatment: starved during the whole experiment; delayed feeding, starved during three days; fed during the enti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…This possibility is also reflected in the morphometric measurements. In fact, the BD was higher in area 5 than in Malta and this parameter is the most responsive to starvation since it depends largely on the cumulative amount of muscle fibers that reflect muscular tissue stored as energy, as it has been indicated by Diaz et al [73] and observed with different species such as, Sparus aurata [74], Miichthys miiuy [75] or Seriolella violacea [76]. Therefore, a better food availability could have compensated for the lower temperature regime in area 5.…”
Section: Discussionmentioning
confidence: 75%
“…This possibility is also reflected in the morphometric measurements. In fact, the BD was higher in area 5 than in Malta and this parameter is the most responsive to starvation since it depends largely on the cumulative amount of muscle fibers that reflect muscular tissue stored as energy, as it has been indicated by Diaz et al [73] and observed with different species such as, Sparus aurata [74], Miichthys miiuy [75] or Seriolella violacea [76]. Therefore, a better food availability could have compensated for the lower temperature regime in area 5.…”
Section: Discussionmentioning
confidence: 75%
“…According to Diaz (2010), Diaz et al . (2013), and Diaz and Macchi (2014), the variables were (Figure 1): standard length ( L S ), length from the snout to the anus (LSA), head depth (HD), body depth at the anus (BDA) and eye diameter (ED). ED was determined as the average between the maximum and minimum diameters.…”
Section: Methodsmentioning
confidence: 98%
“…Slices were observed under optical microscope and a grade of condition was attributed to each larva. Grades were defined based on an extensive review of the literature describing for fish larvae the patterns of histological degradations of criteria commonly used for intestine (midgut and hindgut), pancreas and liver [35,37,70–76]. three grades of condition were then defined as follows:…”
Section: Methodsmentioning
confidence: 99%